Meta‐analysis of patient risk factors associated with post‐bariatric surgery leak. (15th July 2022) - Spiro, Calista; Bennet, Simon; Bhatia, Kiron
Abstract: Objective: Modifiable risk factors such as diabetes, hyperlipidemia, hypertension, obstructive sleep apnea (OSA), chronic kidney disease (CKD), chronic steroid use and smoking, have been shown in observational studies to negatively affect surgical outcomes. The purpose of this study is to identify and determine the effect of modifiable risk factors on post‐operative bariatric surgery leak, as pre‐operative risk modification has been shown to reduce the impact on complications. Methods: Electronic literature searches of MEDLINE, PUBMED, OVID and Cochrane Library databases were performed, including a manual reference check, over the period of 2010 and 2020. 620 articles were screened according to the PRISMA protocol. Results: Twenty articles were included in the meta‐analysis of risk factors. Significant risk factors and the associated effect sizes include: 1. Smoking with an overall OR of 1.31 [1.06, 1.61] and an OR of 1.72 [1.44, 2.05] in Sleeve gastrectomy (SG) patient cohorts; 2. Diabetes with an overall OR of 1.23 [1.08, 1.39] and an OR of 1.33 [1.02, 1.73] in Roux‐en‐Y patient cohorts; 3. Chronic kidney disease with an overall OR of 2.41 [1.62, 3.59] and 4. Steroid use with an overall OR of 1.57 [1.22, 2.02]. Non‐significant risk factors include hypertension with an OR of 0.85, 1.83, OSA with an OR of 1.08 [0.83, 1.39] and hyperlipidemia with an OR of 0.80 [0.61, 1.04]. Combined SG and Roux‐en‐Y patient cohorts with hyperlipidemia have shown a protective effect of 0.78 [0.65, 0.94]. Conclusions: Significant risk factors for leak post bariatric surgery are smoking in all patients and particularly SG patients, diabetes for all patients and particularly Roux‐en‐Y patients, and CKD and chronic steroid for all patients. Hyperlipidemia in two combined patient cohorts (SG and Roux‐en‐Y) appears to have a weak protective effect.